A Visual Tour of Carbon Export by Sinking Particles. Issue 10 (22nd October 2021) - Durkin, Colleen A.; Buesseler, Ken O.; Cetinić, Ivona; Estapa, Margaret L.; Kelly, Roger P.; Omand, Melissa
Abstract: To better quantify the ocean's biological carbon pump, we resolved the diversity of sinking particles that transport carbon into the ocean's interior, their contribution to carbon export, and their attenuation with depth. Sinking particles collected in sediment trap gel layers from four distinct ocean ecosystems were imaged, measured, and classified. The size and identity of particles was used to model their contribution to particulate organic carbon (POC) flux. Measured POC fluxes were reasonably predicted by particle images. Nine particle types were identified, and most of the compositional variability was driven by the relative contribution of aggregates, long cylindrical fecal pellets, and salp fecal pellets. While particle composition varied across locations and seasons, the entire range of compositions was measured at a single well‐observed location in the subarctic North Pacific over one month, across 500 m of depth. The magnitude of POC flux was not consistently associated with a dominant particle class, but particle classes did influence flux attenuation. Long fecal pellets attenuated most rapidly with depth whereas certain other classes attenuated little or not at all with depth. Small particles (<100 μm) consistently contributed ∼5% to total POC flux in samples with higher magnitude fluxes. The relative importance of these small particle classes (spherical mini pellets, short oval fecal pellets, and dense detritus) increased in low flux environments (up to 46% of total POC flux). Imaging approaches that resolve large variations in particle composition across ocean basins, depth, and time will help to better parameterize biological carbon pump models. Plain Language Summary: Sinking particles transport carbon from the surface ocean to depth where carbon is sequestered from the atmosphere for long time periods. The amount of carbon transported by this process is difficult to quantify, in part because of the complex ecological interactions that generate sinking particles and alter downward transport. This study combined chemical measurements with detailed imagery of sinking particles collected in drifting sediment traps to survey how different types of particles affect carbon export across five locations. The biological characteristics of imaged particles can be used to reasonably predict carbon export and its attenuation with depth. Measured particles were classified into nine different categories, including various types of aggregates, organisms, and zooplankton fecal pellets. The amount of sinking carbon was not related to the dominance of any specific particle type, but each type transported carbon with differing efficiencies. Episodic presence of fecal pellets produced by gelatinous zooplankton had a large influence on transport of carbon to depth. Particles often considered too small to contribute to carbon export (<100 µm) were consistently important, especially in low flux environments, and often attenuated relatively little with depth. Resolving biological details of sinking particles improves our ability to quantify the ocean's carbon cycle. Key Points: Carbon flux into the deep ocean by sinking particles can be reasonably predicted from images of collected particle flux Sinking particle type and trophic processing affect attenuation of carbon flux with depth Particles smaller than 100 μm can be an important component of sinking carbon and some attenuated little with depth